Blockholder Disclosure Thresholds and Hedge Fund Activism - Ordóñez-Calafi, Guillem; Bernhardt, Dan (Journal of Financial and Quantitative Analysis, 2022)
Abstract Blockholder disclosure thresholds shape incentives for hedge fund activism, which are jointly determined with real investment and managerial behavior. Uninformed investors value lower thresholds (greater transparency) when the cost of trading against an informed activist outweighs the benefits of the activist’s disciplining of management. Conversely, activists may desire disclosure thresholds if the threat of their participation discourages managerial malfeasance, which is their source of profits. Hedge fund activism can be excessive: If market opacity sufficiently harms uninformed investors, the costs of reduced real investment outweigh the social benefits from managerial disciplining, and society benefits from lower thresholds.